Scrum product owner LiveLessons - Norman, Tommy (Pearson, 2018)
"Scrum Product Owner LiveLessons helps you as a Product Owner understand your role in the Scrum process. It also provides you with tips and practices that Tommy has learned over the years to help you consistently deliver high quality, valuable products to your customers."--Resource description page
Title from title screen (viewed August 23, 2017)
Keywords: Computer software -- Development; Lean manufacturing; Scrum (Computer software development); Agile software development; Production allégée; Scrum (Développement de logiciels); Méthodes agiles (Développement de logiciels); Computer software; Development